Write a Scientific Paper (WASP): An overview of differences in styles between the sciences and the humanities. (February 2019) - Grech, Victor
Abstract: Researchers who cross a discipline may experience culture shock at the different worlds of science and medicine. This paper outlines the differences in concepts and philosophies and in presentation styles. The acute difficulties when attempting to read or write works in different disciplines are also addressed, as well as the differences in perceptions and values when approaching written works in unfamiliar branches of academia.